Effects of Titanium Oxide Nanotube Arrays with Different Lengths on the Characteristics of Dye-Sensitized Solar Cells - Chin-Guo Kuo; Cheng-Fu Yang; Lih-Ren Hwang; Jia-Sheng Huang (International Journal of Photoenergy)
The self-aligned highly ordered TiO2 nanotube (TNT) arrays were fabricated by potentiostatic anodization of Ti foil, and we found that the TNT-array length and diameter were dependent on the electrolyte (NH4F) concentration in ethylene glycol and anodization time. The characteristics of the fabricated TNT arrays were characterized by XRD pattern, FESEM, and absorption spectrum. As the electrolyte NH4F concentration in the presence of H2O (2 vol%) with anodization was changed from 0.25 to 0.75 wt% and the anodization period was increased from 1 to 5 h, the TNT-array length was changed from 9.55 to 30.2 μm and the TNT-array diameter also increased. As NH4F concentration was 0.5 wt%, the prepared TNT arrays were also used to fabricate the dye-sensitized solar cells (DSSCs). We would show that the measured photovoltaic performance of the DSSCs was dependent on the TNT-array length.